Lighthouse museums as Adriatic Sea identity - Babić, Darko muzeolog (2008)
The lighthouses have never been simply navigational tools. Along with their utility function they also encompass many others symbolic values - all of which contribute to their intrinsic heritage quality. Croatian lighthouses are not an exception. However they still do not have an appropriate programme for preservation or interpretation. There are in total 48 lighthouses within the Croatian maritime territory on the eastern Adriatic coast. From the 1990’ s onward all of them were converted to automatic control, although some even today still have keepers. Author, research assistant and lecturer at the Department of Museology of the University of Zagreb propose a new heritage project the "Lighthouse museum".